The Development of Audio-Visual Media-Based Learning Tools on The Subject of Protein Synthesis - Susanti, Wati; Sajiman, Supardi Uki; Leonard, Leonard (Jurnal Report of Biological Education, 2023)
Background: This research aims to develop audio-visual media-based tools on the subject of protein synthesis. Methods: The study design based on the analysis of some of biology material’s characteristic that difficult, rote, and abstract. Data collection was carried out with interviews, questionnaires, and formative tests. Results: Learning tools based on audio-visual media have been successfully developed and obtained as a feasible learning media for learning grade 12 biology. This learning tool was developed with several stages including: needs analysis, selection of materials and tools used to develop media, validation from experts, media improvement based on experts' suggestions and input, and dissemination of media developed by researchers. From the tests conducted by researchers, learning devices based on audio-visual media are very feasible to use. This is based on the overall average of the evaluation results of the four learning devices from the evaluation results by material experts, media experts, and development trials obtained an average score of 94% of the maximum score of 100% so that audio-visual media-based learning devices on the subject of protein synthesis are in the very feasible category. Conclusion: This shows that learning devices based on audio-visual media on the subject of protein synthesis are very feasible to use in learning biology grade 12 SMA. Keywords : Learning tools; audio-visual; protein synthesis